1979
DOI: 10.1111/j.1365-2621.1979.tb08487.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Abilities of Trichloroacetic, Picric, Sulfosalicylic, and Tungstic Acids to Precipitate Protein Hydrolysates and Proteins

Abstract: The abilities of picric, sulfosalicylic (SSA), tricbloroacetic (TCA), and tungstic acids to precipitate a partial hydrolysate of egg albumin and several proteins were examined. After precipitation of the hydrolysate with SSA, TCA, and tungstic acid respectively, it was found that 88%, 79%, and 69% of the nitrogen remained in solution. The average size of the peptides in the supernatants varied from 330 to 380 daltons. The ability to precipitate native proteins varied with the precipitant and the protein. Tungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
3

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 12 publications
1
40
1
3
Order By: Relevance
“…Virtually no reaction was observed, indicating that the supernatant contained oligopeptides with <7-l 5 amino acids (the minimum size required for dye binding, Mayer et al 1986). This result is consistent with those of Greenberg and Shipe (1979), who found that TCA precipitation left dissolved peptides of generally ~4 amino acid residues. Nevertheless, we caution that TCA precipitation is variable in its molecular weight cutoff, depending on factors such as types and concentrations of peptides and other materials in solution.…”
Section: Methodssupporting
confidence: 92%
“…Virtually no reaction was observed, indicating that the supernatant contained oligopeptides with <7-l 5 amino acids (the minimum size required for dye binding, Mayer et al 1986). This result is consistent with those of Greenberg and Shipe (1979), who found that TCA precipitation left dissolved peptides of generally ~4 amino acid residues. Nevertheless, we caution that TCA precipitation is variable in its molecular weight cutoff, depending on factors such as types and concentrations of peptides and other materials in solution.…”
Section: Methodssupporting
confidence: 92%
“…The large peptides of the ␤-casein hydrolysate were precipitated by 5-sulfosalicylic acid (3% final concentration) (12). After centrifugation to remove the 5-sulfosalicylic acid-insoluble peptides, the supernatant was diluted with an equal volume of 100 mM lithium chloride-68.5 mM sodium citrate (pH 2.2) and filtered through a 0.45-m-pore-size filter (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to dietarv Drotern. this system is designed to fractionare into ruminaliy degrad_ able and undegradabie protein and into unavailabie p.ot"in (Chalupa 1992 Roe et al (1990). Non-protein nitrogen content was estimated using sodium tungstate as a precipitating agent according to the procedure of Greenberg and Shipe (1979 HFCM hadhigher (P < 0.05) calcium (Ca) and lower (P < 0.05) phosphorus (P) and magnesium (Mg) levels relative to LFCM and higher (P < 0.05) Ca and lower (P < 0.05) P contents relative to regular canola meal (Table 3). No differences were observed in mineral composition between regular canola meal and LFCM except for P which was higher (P < 0.05) in LFCM relative to regular canola meal.…”
mentioning
confidence: 99%